Survival of the fittest : The shifting contours of higher education in China and the United States - Gerstl-Pepin, Cynthia; Li, Qi (New Frontiers of Educational Research, 2014)
This book will examine how universities in China and the US are responding to markets and increasing global competition. For both countries, a university education is seen as key to economic development. While China and the US have two very different political systems, they represent the two largest economies in the world and share beliefs that higher education plays an integral role to economic development. The book will bring together scholars with multiple perspectives on the topic to create dialogue around similarities and differences. This book will appeal to students, scholars, and higher educational administrators in both countries and other countries as well who are seeking to understand the strategic change in higher education in both China and the US.